Force-cvelocity-power profile in high-elite boulder, lead, and speed climber competitors - Levernier, G.; Samozino, P.; Laffaye, G. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To compare the force-production capacities among boulderers, lead climbers, and speed climbers during a pull-up test using a force-velocity-power profile. Methods: In total, 24 high-elite climbers (11 boulderers, 8 lead climbers, and 5 speed climbers) did 2 pull-ups at different percentages of their body mass (0%, 30%, 45%, 60%, and 70%). Force-velocity-power profile analyses were performed with the use of an accelerometer for each load. The intraclass correlation and coefficients of variation were calculated. A 1-way analysis of variance was performed with a Tukey post hoc test to assess the difference between the groups. Results: Regarding force, the coefficient of variation ranged from 1.00% to 6.18% and the intraclass correlation ranged from .98 to .99. For velocity, the coefficient of variation ranged from 2.75% to 6.62% and the intraclass correlation ranged from .84 to .95. The linear regression slope showed R2 to be between .93 and .99, confirming the high quality of the linear relationship between velocity and the external force produced during a pull-up. Boulderers presented significantly higher (P<.05) maximal power (+22.30% and +26.29%), mean power for the pull-up at body weight (+23.49% and +25.35%), and theoretical maximal velocity at zero force (+23.92% and +21.53%) than lead and speed climbers and a more significant curve increase (+35.21% compared with lead climbers). Conclusions: The reliability of the method was shown to be high. Moreover, boulderers were able to develop an important external force and had the capacity to maintain high speed when force production increased.